Sonographic Assessment of the Fetal Penile Development. (3rd March 2016) - Akpinar, Funda; Yilmaz, Saynur; Akdag Cirik, Derya; Kayikcioglu, Fulya; Dilbaz, Berna; Yucel, Husniye; Gelisen, Orhan
Abstract: The intrauterine diagnosis of micropenis is an important clue in the discernment of some syndromes and hormonal deficiencies. In this study, we tried to establish reference ranges for the fetal penile length and penile width. This prospective cross-sectional study included 179 healthy singleton male fetus pregnancies that were between 17 and 37 weeks of gestation. Of these pregnancies, the fetal penile length and width were measured using trans-abdominal ultrasound. The correlation coefficients of gestational age with penile measurements were calculated. We observed that as the gestational age increased both the penile length and width increased ( p < .0001, correlation coefficients R 2 = 0.854 and R 2 = 0.883; respectively). Reference values of the penile length in the Turkish Population were similar to previously evaluated populations including English, American and Israeli populations. The penile width measurement is a convenient way to diagnose micropenis, but penile width measurement alone might miss some penile abnormalities including chordee and hypospadias.